Racial differences in abdominal depot-specific adiposity in white and African American adults - Katzmarzyk, Peter T; Bray, George A; Greenway, Frank L; Johnson, William D; Newton, Jr, Robert L; Ravussin, Eric; Ryan, Donna H; Smith, Steven R; Bouchard, Claude (The American journal of clinical nutrition, 2010)
There is increasing interest in understanding racial differences in adiposity in specific body depots as a way to explain differential health risks associated with obesity. Our aim was to examine the differences in abdominal visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) between white and African American adults. The sample included 1967 adults aged 18-84 y, including 790 white women, 435 African American women, 606 white men, and 136 African American men. Total body fat was measured by using dual-energy X-ray absorptiometry, whereas abdominal VAT and SAT cross-sectional areas (L4-L5 level) were measured by using computed tomography. Sex-specific differences in SAT and VAT between racial groups were analyzed by the use of general linear models, which controlled for age and total body fat. Additional models tested for racial differences in VAT and SAT and controlled for age, total body fat, smoking, and menopausal status. Statistical significance was accepted at P < 0.05. Abdominal VAT was significantly higher in white than in African American men and women, even after adjustment for covariates. White women had significantly lower SAT than did African American women, both before and after adjustment for covariates. White men had significantly higher SAT than did African American men, but after adjustment for covariates, their SAT was lower than that of African American men. Abdominal visceral adiposity is significantly greater in white men and women. After adjustment for covariates, white men and women had significantly lower SAT than did African American men and women. The results of this study highlight the heterogeneity of human body fat distribution across racial groups.This trial was registered at clinicaltrials.gov as NCT00959270.